Higher Education Institutions and Digital Transformation: Building University-Enterprise Collaborative Relationships - Marcin Lis (Routledge, 2023)
The growing complexity, fluidity and instability of the environment as well as changing needs are challenges that both enterprises and higher education institutions must face. Higher education institutions understand that their key product, i.e. knowledge, is a value that can and should be offered to enterprises in a desirable form as a key to innovation and development as well as the basis of the necessary internal transformation to respond to requirements of our times. Attempts to explain the process of collaboration between higher education institutions and businesses based on an institutional perspective fail to capture the complexity of this process. The purpose of this book is to develop a model approach to managerial competencies that affect the innovativeness of enterprises and to identify internal and external key factors strengthening or limiting the impact of managerial competencies on the innovativeness of an enterprise including organizational structure, strategy, organizational culture and more. It will be of value to researchers, academics, and students in the fields of entrepreneurship, innovation, management, strategy, and will be particularly useful to organizations that are aware of their operating conditions in the knowledge-based economy and of the impact of the COVID-19 pandemics on the acceleration of the digital transformation of the contemporary world. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons (CC-BY-NC-ND) 4.0 license.
Keywords: 650; businesses; digital technologies; digital transformation; governance; higher education institutions; knowledge-based economy; marketing; relationship building; relationship management; universities